TEACHERS’ PERCEPTIONS REGARDING THE EFFECTIVENESS OF PHYSICAL EDUCATION (PJOK) INSTRUCTIONAL METHODS IN SCHOOLS WITH LIMITED FACILITIES AND INFRASTRUCTURE - Prita Yunita; Gatot Jariono; Pungki Indarto (Program Studi Pendidikan Jasmani, FKIP Universitas Bina Bangsa Getsempena, 2026)
The effectiveness of instructional implementation in Physical Education, Sports, and Health (PJOK) subjects is assessed from the teachers’ standpoint, while considering the constraints of supporting infrastructure, particularly the unavailability of a sports field, within the context of SMA Muhammadiyah 1 Surakarta. This research adopts a descriptive quantitative design utilizing a survey method, involving the entire teacher population of thirty-nine participants, comprising both physical education educators and teachers of other disciplines. Data were gathered through a validated and reliable questionnaire and subsequently processed using descriptive statistical analysis.The findings reveal that teachers’ perceptions of overall instructional effectiveness are categorized as good (68.67%). The internal teacher-related dimension records the highest achievement (71.92%), followed by external influencing factors (69.70%), and the effectiveness of teaching methods alongside learning outcomes (69.17%). Nevertheless, there exists a mutual recognition of a disparity between policy support and the adequacy of available facilities, with nearly half of the respondents expressing agreement regarding limitations in infrastructure. These results suggest that although teachers demonstrate strong competence and adaptability, the optimization of learning processes remains constrained by infrastructural inadequacies. Accordingly, this study emphasizes the necessity of strategic collaboration and the integration of technological solutions to bridge this gap, thereby allowing teachers’ potential to be more fully actualized.